CIMETID1NE ENHIBITS ELIMINAT1ON OF SULPHAMETHOXAZOLE IN RABBIT {Oryctolagus Cuniculus) - Ida Tjahajati (Jurnal Sain Veteriner, 2000)
Cimetidine was reported to inhibit elimination many other drugs. The research has been done to study the effect of cimetidine on elimination of sulphamethoxazole in rabbits. Twenty healthy male rabbits, 10 months of age were used as experimental animals. The rabbits were allotted into 4 groups of 5 each Group I as a control group were intramuscularly injected with 25 mg sulphamethoxazole. Group 11 were intramuscularly injected 25 sutphamethoxazole and pretreated with 12.5 mg cimetidine 30 minutes before injection. Group 111 were intramuscularly injected 25 mg sulphamethoxazole, pretreatod with 25 mg cimetidine 30 minutes before injection. Group IV were intramuscularly injected 25 mg sulphamethoxazole, pretreated with 50 mg cimetidine 30 minutes before injection. Blood sample were collecled at 0.25, 0 75, 1,75, .1.75, 10 and 24 hours after injection. Plasma sulphamethoxazole levels were determined using the Bratton-Marshall method Elimination kinetic parameters were analyzed statistically using anava. The result of the study showed that cimetidine significantly reduced total clearance of sulphamethoxazole <P<0.l). Based on the result it can be concluded that cimetidine inhibits elimination of sulphamethoxazole.